Holoprosencephaly with agenesia of the prosencephalic ventricle - Laure-Kamionowska, Milena; Szymanska, Krystyna; Klepacka, Teresa (Folia Neuropathologica, 2015)
Malformations of the forebrain are characterized by abnormalities in size, shape, and arrangement of the cerebral hemispheres and ventricles. We present the morphological picture of a brain with failure of the forebrain complementary to holoprosencephaly coexisting with absence of the anterodorsal part of the prosencephalic ventricles. The anomaly can be graded within the holoprosencephalic spectrum due to the main morphological features. However, such alterations as aplasia of the forebrain ventricles and prominent leptomeningeal gliomesodermal proliferation are related to atelencephaly. The observations confirm the common pathogenic mechanism of aprosencephaly/atelencephaly and holoprosencephaly. The malformation corresponds to a wide continuous spectrum with no clear-cut boundaries of abnormal formation of the prosencephalon.